The Development of E-Worksheet Integrated With Virtual Laboratory to Train Student’s Scientific Literacy Skills on Blood Circulatory System Topic - Mahda Rizqina Maftuha; Sifak Indana (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
The use of technology in online learning during the covid-19 pandemic is needed due to provide facilities for students in learning activities. Scientific literacy skills is included in higher-order thinking skills by the demands of the implementation curriculum 2013. Data in the field showed that the majority of students in Indonesia have a low level of scientific literacy. The purpose of this research was to make an e-worksheet integrated with Virtual Laboratory to train Scientific Literacy Skills on Circulatory System Materials that feasible, practical, and effective. The research model was 4D (Define, Design, Develop, Disseminate). The research trial was conducted on 18 students of SMAN 1 Pasuruan. The validity of the e-worksheet has been known from the results of the validation by the validators, the practicality of the e-worksheet has been known from the results of student response questionnaires, and the effectiveness has been known from the learning outcomes refers to scientific literacy indicators.. Data analysis was carried out with a quantitative description. The results of e-worksheet validation were 94.62% which is a very valid category. The results of the practicality were 95.1% in the very practical category, and the effectiveness results were 88% which is in the very effective category. Based on the results obtained, e-worksheet integrated with virtual laboratory to train scientific literacy on circulatory system was valid, practical, and effective. Keywords: Scientific literacy, E-worksheet, Virtual laboratory